Efecto del diálogo socrático en las competencias comunicativas lectoras de los estudiantes de noveno grado de la Institución Arcesio Cáliz (2017)
In this research, the use of the Socratic Dialogue is determined as a strategy to improve the development of reading skills in students of the ninth grade of the Arcesio Cáliz Amador Departmental Educational Institution of the Municipality of El Banco Magdalena. The objective of this study is to identify the effect of the Socratic dialogue on the reading skills of students between the ages of fourteen and seventeen. The research is of a quantitative approach, framed in a quasi-experimental methodological design, with a population of 120 students and it was taken a non-probabilistic sample consisting of 20 students of the 9th grade of the afternoon session. A diagnostic test was performed in which difficulties were identified in the three components of reading skills such as the Semantic, Syntactic and Pragmatic. Then it starts a phase of the activities and readings for the respective intervention, finally workshops were designed and applied which show as a result greater capacity of the students in the three components evaluated in the reading competences when it is compared with the students that did not intervene. For this reason, it is concluded that the use of the Socratic Dialogue is a fundamental tool that improves the development of reading skills of students in its three components.